Early origin and evolution of the FtsZ/tubulin protein family - Santana-Molina, Carlos; Saz-Navarro, DMaría del; Devos, Damien P. (Frontiers in Microbiology, 2023)
The origin of the FtsZ/Tubulin protein family was extremely relevant for life since these proteins are present in nearly all organisms, carrying out essential functions like cell division, or forming a major part of the cytoskeleton in eukaryotes. Therefore, investigating the early evolution of the FtsZ/Tubulin protein family could reveal crucial aspects of the diversification of the three domains of life. In this study, we revisited the phylogenies of the FtsZ/Tubulin protein family in an extensive prokaryotic diversity, focusing on the main evolutionary events that occurred during its evolution. We found evidence of its early origin in the last universal common ancestor, since FtsZ was present in the last common ancestor of Bacteria and Archaea. In bacteria, ftsZ genes are genomically associated with the bacterial division gene cluster, while in archaea, ftsZ duplicated prior to archaeal diversification and one of the copies is associated with protein biosynthesis genes. Archaea have expanded the FtsZ/Tubulin protein family with sequences closely related to eukaryotic tubulins. In addition, we report novel CetZ-like groups in Halobacterota and Asgardarchaeota. Investigating the C-termini of prokaryotic paralogs basal to eukaryotic tubulins we show that archaeal CetZ as well as the plasmidic TubZ from Firmicutes, most likely originated from archaeal FtsZ. Finally, prokaryotic tubulins are restricted to Odinarchaeaota and Prosthecobacter species and they seem to belong to different molecular systems. However, their phylogenies suggest that they are closely related to α/β-tubulins pointing a potential ancestrality of these eukaryotic paralogs of tubulins.